2020
DOI: 10.3390/w12092384
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Biogeochemical Impacts of Fish Farms Using a Benthic-Pelagic Model

Abstract: Sustainable development of the salmon farming industry requires knowledge of the biogeochemical impacts of fish farm emissions. To investigate the spatial and temporal scales of farm impacts on the water column and benthic biogeochemistry, we coupled the C-N-P-Si-O-S-Mn-Fe transformation model BROM with a 2-dimensional benthic-pelagic transport model (2DBP), considering vertical and horizontal transport in the water and upper 5 cm of sediments along a 10 km transect centered on a fish farm. The 2DBP model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Deposition rates up to 70 g DW m −2 d −1 were measured in the vicinity of a farm in a shallow location, with high production levels (Keeley et al 2019). A severe im pact of intensive production farms is generally associated with poor currents and water circulation, which may drastically damage benthic ecosystems due to the lack of oxygen in the sediment (Soto & Norambuena 2004, Yakushev et al 2020). The protection of vulnerable ecosystems is of major concern and farms are now monitored regularly to assess their impacts on the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition rates up to 70 g DW m −2 d −1 were measured in the vicinity of a farm in a shallow location, with high production levels (Keeley et al 2019). A severe im pact of intensive production farms is generally associated with poor currents and water circulation, which may drastically damage benthic ecosystems due to the lack of oxygen in the sediment (Soto & Norambuena 2004, Yakushev et al 2020). The protection of vulnerable ecosystems is of major concern and farms are now monitored regularly to assess their impacts on the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional mathematical model of biogeochemical cycles, combined with the model of hydrodynamics, used in this work, makes it possible to predict the spatialtemporal dynamics of the main phytoplankton populations more accurately compared to the two-dimensional models discussed above [12,13,15,16], taking into account the changing hydrological regime, their consumption of nutrients, the transition of nutrients from one form to another. In contrast to the two-dimensional model used in [14], the three-dimensional model of hydrodynamics makes it possible to more accurately model wave processes under conditions of a complex, dynamically changing the geometry of the reservoir, friction on the bottom and wind stress on the free surface, turbulent and advective heat and mass transfer in three coordinate directions, Coriolis forces, river flows, precipitation and evaporation, heat and salt transportation.…”
Section: Discussionmentioning
confidence: 99%
“…Biogeochemical processes in marine ecosystems are modeled by Norwegian scientists together with Russian researchers. Therefore, in work [15], the complex of C-N-P-Si-O-S-Mn-Fe transformation model BROM and the 2-dimensional benthic-pelagic transport model (2DBP) were applied to analyze the impact of salmon farms on the water column and benthic biogeochemistry. Hydrophysical model data for the Hardangerfjord in western Norway were applied for the 2DBP model.…”
Section: Introductionmentioning
confidence: 99%
“…Many Norwegian salmon farms are located in fjords, and studies have shown that warming is leading to reduced oxygen levels in some areas [55]. Deoxygenation can reduce assimilative capacity [55,116]. Precipitation and runoff will contribute organic matter to the fjord or coastal environment and the associated microbial activity could affect overall assimilative capacity of the environment [117].…”
Section: Plos Climatementioning
confidence: 99%